HUBUNGAN KELEMBABAN DAN KEBIASAAN MEROKOK PENGHUNI DI DALAM RUMAH DENGAN PENYAKIT ISPA PADA BALITA - ullya; Sari, Rosdiana Sefti Eka (Jurnal Sanitasi Profesional Indonesia, 2021)
Acute Respiratory Infection (ARI) is a global concern because it is one of the main causes of death in children under five years old (toddlers) in the world. In Indonesia ARI cases always rank first in the cause of infant mortality. In addition, ARI is often on the list of the ten most afflicted diseases in hospitals and health centers. Based on the profile of Bengkulu Province Health in 2017, as for the 10 highest diseases based on the illness data of the ISPA puskesmas occupy the first position. Several factors such as humidity in the house and occupant smoking habits in the house are thought to be risk factors for the occurrence of ARI disease. The purpose of this study was to determine the relationship of humidity and smoking habits of residents in homes with ARI disease in Kelurahan Kebun Kenanga, Bengkulu City. Crossectional research design with 124 samples. The research instrument used was moisture measurement with thermohygrometer and questionnaire. Data analysis was done by univariate and bivariate using the chi square test with a value of pvalue <0.05. The results of this study indicate that there is a relationship between humidity and ARI disease (pvalue =0.007), and indicates that there is a relationship between occupants' smoking habits in homes with ARI disease (pvalue = 0.021). The results of the univariate analysis, most (68%) had moisture did not meet the requirements, most (69%) respondents smoked inside the house. most (31%) toddlers experience moderate ISPA pain, the community, especially the respondents in this study pay more attention to what can affect the occurrence of ARI disease or that can worsen the condition of infants affected by ARI.